A model of viscoelastoplasticity in the cochleo‐saccular membranes - Daniel J. Pender (Laryngoscope Investigative Otolaryngology, 2019)
Introduction Variations in the distensile behavior of the cochleo‐saccular vestibular membranes may contribute to lesion evolution of endolymphatic hydrops in Meniere's disease. Such variation may be mediated through membrane viscoelastoplasticity. This feature may provide insight into the distensile process at work in these membranes. Hypothesis A precipitated collagen matrix can provide a suitable in vitro model of viscoelastoplasticity in cochleo‐saccular vestibular membranes. Methods An in vitro extra‐cellular matrix of precipitated collagen was evaluated as a model of suspected viscoelastoplastic behavior in the cochleo‐saccular vestibular membranes. The structure of the precipitated collagen was assessed for its similarity to that of the basal lamina of the pars inferior vestibular membranes. The biomechanics of this matrix were scrutinized for evidence of viscoelastoplastic distensile properties. Results A matrix of precipitated collagen was found to exhibit a mesh‐like fibrous structure similar to that of collagen found in the basilar lamina of the cochleo‐saccular vestibular membranes. This matrix was also found to exhibit a sigmoid distensile response as well as strain rate sensitivity, both of which are characteristic properties of polymer viscoelastoplasticity. Conclusions An in vitro matrix of precipitated collagen appears to provide a suitable model that can account for variations in the distensile behavior of the cochleo‐saccular vestibular membranes. The model exhibits viscoelastoplasticity and may have heuristic value in the analysis of lesion evolution in Meniere's disease. Level of Evidence 6